TRADITION OF "DINAH BEGUS" IN THE CONSTRUCTION OF HOUSES: Analysis of Islamic Perspectives and the Integration of Local Wisdom in Ponteh Galis Pamekasan - Rosi, Muhammad Fathur; Anam, Syaiful; Suhaimi, Suhaimi; Marsum, Marsum (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2025)
This research aims to examine the tradition of Dinah Begus in the construction of houses in Ponteh Village, Galis, Pamekasan, and analyze it from an Islamic perspective. Dinah Begus is a local tradition that has been passed down from generation to generation, where people choose a good day as the right time to start important activities, such as building a house. This belief is based on the hope of blessings, safety, and smoothness in the development process and life in the future. This research uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation studies to understand the practices, symbols, and meanings contained in the tradition. The results of the study show that Dinah Begus contains noble values such as prudence, spirituality, and respect for ancestral traditions. From an Islamic perspective, this practice is not contradictory as long as it is not accompanied by shirk beliefs, but is understood as a form of effort in determining the time that is considered most appropriate based on people's experiences and habits. This research is expected to contribute to the preservation of local culture that is in harmony with Islamic values, as well as enrich the study of the interaction between religion and tradition in Madurese society.